Pengaruh Social Media Influencer, Persepsi Risiko, dan Ekspektasi Return terhadap Keputusan Investasi - A. Ahsan Amir; Bandang, Agus; Ulman Idris, Muhammad Istiyansyah (Accounting Department, Faculty of Economics and Business, Universitas Hasanuddin, 2024)
This study examines and analyze the influence of social media, perceived risk, and expected return on investment decisions in the capital market. The independent variables in this study are social media influencers, risk perceptions, and return expectations, while the dependent variable is investment decisions. This study used a survey method by delivering questionnaires to investors in Makassar City. The sample was determined using the Slovin formula,sampling used a purposive sampling technique, and then data were compiled to be analyzed using multiple linear regression. The number of samples in this study was 100 respondents from the entire population. The regression test results showed that social media influencers and return expectations affect investment decisions in the capital market. At the same time, risk perception does not affect investment decisions in the capital market. Test result together reveal that social media influencer, risk perception and expected return accordingly influencer investment decision in the capital market.